The market for salmon futures: an empirical analysis of the Fish Pool using the Schwartz multi-factor model. Issue 12 (1st December 2016) - Ewald, Christian-Oliver; Nawar, Roy; Ouyang, Ruolan; Siu, Tak Kuen
Abstract : Using the popular Schwartz 97 two-factor approach, we study future contracts written on fresh farmed salmon, which have been actively traded at the Fish Pool Market in Norway since 2006. This approach features a stochastic convenience yield for the salmon spot price. We connect this approach with the classical literature on fish-farming and aquaculture using first principles, starting by modelling the aggregate salmon farming production process and modelling the demand using a Cobb–Douglas utility function for a representative consumer. The model is estimated by means of Kalman filtering, using a rich data-set of contracts with different maturities traded at Fish Pool between 12 June 2006 and 22 June 2012. The results are then discussed in the context of other commodity markets, specifically for live cattle which acts as a substitute.